Proteome and Protein Network Analyses of Memory T Cells Find Altered Translation and Cell Stress Signaling in Treated Human Immunodeficiency Virus Patients Exhibiting Poor CD4 Recovery. (15th March 2016) - Azzam, Sausan; Schlatzer, Daniela; Maxwell, Sean; Li, Xiaolin; Bazdar, Douglas; Chen, Yanwen; Asaad, Robert; Barnholtz-Sloan, Jill; Chance, Mark R.; Sieg, Scott F.
Abstract: Background. Human immunodeficiency virus (HIV) patients who experience poor CD4 T-cell recovery despite viral suppression during antiretroviral therapy (ART) are known as immunological nonresponders. The molecular mechanism(s) underlying incomplete immune restoration during ART is not fully understood. Methods. Label-free quantitative proteomics on single-cell type central memory T cells were used to reveal relative protein abundance changes between nonresponder, responder (good CD4 recovery during ART), and healthy individuals. Proteome changes were analyzed by protein pathway and network analyses and verified by selected reaction monitoring mass spectrometry. Results. Proteomic analysis across groups detected 155 significant proteins from 1500 nonredundant proteins. Pathway and network analyses revealed dysregulation in mammalian target of rapamycin and protein translation-related proteins and decreases in stress response-related proteins for nonresponder subjects compared with responders and controls. Actin cytoskeleton signaling was increased for HIV responders and nonresponders alike. Conclusions. Memory T cells from immunologic nonresponders have increases in proteins related to motility and protein translation and decreases in proteins capable of responding to cellular stresses compared with responders and controls. The potential for T cells to manage stress and modulate metabolism may contribute to their capacity to reconstitute a lymphopenic host.